Media Promosi Kesehatan Dengan Permainan Ular Tangga Terhadap Sikap Santri Dalam Pencegahan Scabies Di Pesantren Kota Banda Aceh - Dewi Sartika; Cut Oktaviyana (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
The high prevalence of Scabies is due to the lack of attitude and poor environmental sanitation conditions. The lack of these will lead to the emergence of bad habits, such as poor personal hygiene, which can cause the body to be attacked by skin diseases that often occur in students, such as Scabies. This research aimed to determine the effect of snakes and ladder game media on the attitude of students in preventing Scabies at the Babun Najah Islamic Boarding School of Banda Aceh. This research used quasi-experimental methods with the pretest and post-test control group design. The population in this research was 53 students, while the sample was 15 students chosen by the Simple Random Sampling technique. The research instrument used a questionnaire to determine attitude of students about scabies prevention. the Likert scale to assess students' attitudes. This research was conducted at Babun Najah Islamic Boarding School of Banda Aceh on August 18, 2023. The analysis using the t-test obtained a -value of 0.002 < α = 0.05 for attitudes, thus indicating that Ho was rejected, and Ha was accepted. This research concludes that there is a correlation between snakes and ladder game media on the attitude of students in preventing Scabies at the Babun Najah Islamic Boarding School of Banda Aceh. The researcher suggests that the Islamic boarding school can maintain the cleanliness of students to avoid Scabies.